The Ethics of Canadian Entry-To-Practice Pain Competencies: How Are We Doing? - Judy Watt-Watson; Elizabeth Peter; A John Clark; Anne Dewar; Thomas Hadjistavropoulos; Pat Morley-Forster; Christine O’Leary; Lalitha Raman-Wilms; Anita Unruh; Karen Webber; Marsha Campbell-Yeo (Pain Research and Management)
BACKGROUND: Although unrelieved pain continues to represent a significant problem, prelicensure educational programs tend to include little content related to pain. Standards for professional competence strongly influence curricula and have the potential to ensure that health science students have the knowledge and skill to manage pain in a way that also allows them to meet professional ethical standards.